The Expression of National and Personal Identity in Béla Bartók’s Music - Vikárius, László (Danish Yearbook of Musicology, 2005)
The article explores the significance of musical, specifically melodic, characteristics of ethnic definition in Béla Bartók’s music. The argument is principally based on two sets of closely related examples. First, revisiting Bartók’s first major work the Kossuth Symphony (1903), written to depict and commemorate the 1848-49 Hungarian war of independence, his youthful musical nationalism (or patriotism) is discussed. An analysis of some of its central themes – those representing Lajos (Louis) Kossuth, the leader of the uprising, the Hungarian heroes and, as a contrast, that of the Austrian enemy (this latter famously parodying Haydn’s ‘Gott erhalte’) – reveals not only the presence of musical stereotypes but also the strategic importance of motif transformation, a technique that was to remain crucial for Bartók’s later (‘mature’) composition, too. Furthermore, although this overtly political work belongs to the very beginning of Bartók’s professional career, a period many of whose compositional solutions and the Kossuth itself he categorically rejected within a few years, his commitment to the employment of ethnic musical characteristics in his music proved to be central to his thinking. His main achievement lies, obviously, in the varied use of the newly discovered indigenous folk material from a number of different sources most notably Romanian and Slovak, apart from the Hungarian, thereby representing multiculturalism at an unparalleled level in the period. Still, there are significant moments where his Hungarian identity seems to prevail. Thirty years ago, László Somfai pointed out one such moment by describing what he called the ‘Hungarian culmination point’ characteristic of several of Bartók’s compositions. The second part of the article examines ‘Hungarian’ characteristics in a melody type recurring from the First String Quartet (1908-9) to the last compositions, the Solo Violin Sonata (1944) and the Third Piano Concerto (1945), and most memorably present in the slow sections of ‘Evening at the Village’ and in the ritornello theme of the Dance Suite (1923). Interestingly, however, the repeated use of the melody type may have been dictated by its ‘national’ as much as by its ‘personal’ and biographical significance.